THE ETHICS OF THE USE OF ARTIFICIAL INTELLIGENCE IN THE DEVELOPMENT OF INFORMATION TECHNOLOGIES - Унгурян, Галина (SWorldJournal, 2025)
The widespread use and application of AI has increased the efficiency of work in various areas of life, in particular, AI has been used in web design, finance, programming, healthcare and education. Its widespread use increases the efficiency of work and